Selected Decisions from the Federal Supreme Court Cassation Bench - Chane, Gizachew Silesh (Bahir Dar University Journal of Law, 2022)
These case reports are selected from the cassion decision of the Federal Supreme Court of Ethiopia, which renders binding interpretation of laws.